Cerebrospinal fluid adenosine deaminase isoenzymes in meningeal tuberculosis diagnosis - Barrón-Pastor, Helí Jaime (2012)
detection and immediate installation of appropriate therapy. Given the low sensitivity of sputum smear and culture of bacillus tuberculosis, other tools should be explored in the differential diagnosis of tuberculous meningitis such as adenosine deaminase (ADA) isoenzymes. Objectives: To determine ADA isoenzymes activity in cerebrospinal fluid (CSF) of patients with tuberculous meningitis. Design: Descriptive study, with non-probability sampling. Institution: Biochemistry and Nutrition Research Center, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biological materials: Samples of CSF from patients with clinical symptoms of tuberculous meningitis. Interventions: Samples of CSF with ADA activity above 9 U / L were stored at -40°C until vertical electrophoresis was run. Mann - Whitney statistical analysis was used with 0.1 significance level to compare meningeal tuberculosis ADA values with other nervous system diseases. Main outcome measures: Isoenzymes ADA1m, ADA1cp, and ADA2. Results: Median total ADA enzyme activity in CSF in all patients with TB meningitis was higher than in other parainfective diseases of the central nervous system. In both cases ADA1cp had greater contribution to total ADA and showed larger increase in tuberculous meningitis. ADA2 increase was higher in meningeal tuberculosis compared with other CNS diseases. Conclusions: CSF electrophoresis distinguishes ADA isoenzymes, showing elevated levels of ADA2 in meningeal tuberculosis as a result of increased monocyte-macrophage cell line.